With Collies Graven on His Heart: The Canine Projections of Thomas Anstey Guthrie (1856–1934) - Peter Merchant (Cahiers Victoriens et Edouardiens)
Soon after adopting ‘F. Anstey’ as his nom de plume, Thomas Anstey Guthrie (1856–1934) scored a striking success with his début novel Vice Versâ (1882). On a necessarily smaller scale, he then repeated the feat months later with his short story ‘The Black Poodle’. By writing in the novel about a boys’ school (though with a touch of magical mystery) and by centring the story on a dog (though with a distinct sting in the tail), he demonstrated how well attuned he was to the taste of the times. The recourse had by the plots of both to doubles and stand-ins means that ‘The Black Poodle’ trots in the footprints of Vice Versâ. It is also a prospective epitome of Anstey’s mature work, pointing a direction for much in his subsequent career. In 1920 he came back round to it with a vengeance, embarking on a silent film scenario which reprises the original storyline. The 1920 script gives this an unexpected extension, however, as if to teach the old dog some new tricks. On many other occasions Anstey applied in a more general way what writing the story had taught him about the value of having his exploration of human nature and human emotions refracted through canine experience. The reasons for which Anstey so badly needed dogs both in his life and in his work can be inferred from his autobiography, and from the most personal of his unpublished writings. It was indeed as doubles and stand-ins that they came to serve him. As he grew more deeply attached to the dogs he owned, and increasingly inclined to identify both himself and his loved ones with them, so he transferred to them the griefs with which he could not otherwise deal. In the end he perhaps depended on that displacement for his ability to function, or his ability to continue coming across, as the comic writer whom the success of Vice Versâ had brought to birth.